Level of Cultural Attachment Among English-Dominant Malaysian Chinese University Students - Al-Saggaf, Mohammad Ali; Su, Yaqi (Advances in Humanities and Contemporary Studies, 2024)
In an era of rapid globalization and sociocultural transformations, understanding the impact of language dominance on cultural identity is crucial. This study addresses the under-explored area of the attachment of English-dominant Malaysian Chinese (EMC) university students to Malaysian Chinese Culture (MCC). Despite English’s growing prominence in Malaysia, there is a paucity of research investigating its effect on EMCs’ cultural attachments. Contrasting to the predominantly qualitative methods in the research filed, our research adopts a quantitative approach, offering an objective assessment of EMC students’ cultural attachment. The study involved 74 participants, selected through purposive sampling, who completed a 12-item online questionnaire. The questionnaire adapted the Multigroup Ethnic Identity Measure (MEIM) as the Malaysian Chinese Cultural Identity Measure (MCCIM), validated through a pilot test with the Cronbach α score of 0.830. The results indicate a positive attachment of these students to MCC, suggesting resilience in cultural identity despite the predominance of English. This research contributes to the broader discourse on cultural identity preservation within the landscape of language shifts, offering a foundation for future studies in similar multicultural and multilingual settings.